Effect of Lime and Integrated Nutrient Management on Soybean under Rainfed Condition of Nagaland - Lynrah, Anniecia; Nongmaithem, D. (International Journal of Bio-resource and Stress Management, 2017)
A field experiment was conducted in the Experimental Research Farm of School of Agricultural Sciences and Rural Development (SASRD), Nagaland University during the kharif season of 2015 to study the effect of lime and integrated nutrient management on soybean under acidic soil of Nagaland. The results revealed that application of lime @ 1.5 t ha-1 gave highest values of growth and yield attributes. The number of primary branches plant-1, dry weight of plant, crop growth rate, fresh weight of nodules plant-1, number of pods plant-1, pod length were obtained with the application of lime @1.5 t ha-1 and hence recorded highest seed (2.71 t ha-1) and stover yield (2.79 t ha-1). The uptake of NPK by soybean was also found to be highest under application of lime @ 1.5 t ha-1. Among the nutrient sources, application of 50% RDF+Rhizobium @ 20 g kg-1 seed+Phosphate solubilising bacteria (PSB) @20 g kg-1 seed gave the best results in terms of growth attributes and recorded the highest yield and nutrient uptake by the crop which was followed by 50% RDF+FYM @ 5 t ha-1+Vermicompost @ 2 t ha-1.The treatment combination of 1.5 t ha-1 of lime with 50% RDF+Rhizobium @ 20 g kg-1 seed+Phosphate solubilising bacteria (PSB) @20 g kg-1 seed gave the highest gross and net return with B:C ratio of 1.83 among all the treatment combinations and thus was found to be most economical treatment for soybean under rainfed condition of Nagaland.